Examining the Long-Run and Short-Run Effects of Technical and Financial Factors on Bitcoin Blockchain Network Transaction Fees - Amin Rostami; Mahdi Safaei (Journal of Asset Management and Financing)
In recent years, Bitcoin has garnered increasing public and media attention, as well as investment in this field. This cryptocurrency currently has the highest market value among existing virtual currencies that can operate in a decentralized manner based on defined incentives. These incentives include a fixed mining reward for each block and a variable reward resulting from transaction fees in the blockchain network. The transaction fee in the Bitcoin network is unstable and is determined in real-time. Due to the reduction of the fixed mining reward, the transaction fees have become the primary source of income for miners. This study examined the long-term and short-term effects of technical and financial factors on user behavior in determining Bitcoin transaction fees. The autoregressive distributed lag (ARDL) model was used for this analysis. The dataset spanned from April 10, 2018, to July 24, 2023. The technical factors examined included the average daily block size in bytes, network difficulty, and daily transaction volume. The financial factors included the average daily value of transactions sent to Bitcoin and the average daily Bitcoin price in dollars. The results showed that the technical factor of network difficulty had the greatest long-term impact on transaction processing fees. Additionally, the average daily block size in bytes had a significant long-term impact on transaction fees. However, the Bitcoin price did not have a significant long-term impact on transaction fees. These findings can help users make more informed decisions when setting transaction fees. Additionally, the results can assist miners in adopting better strategies to maximize their earnings.